2010
DOI: 10.1002/ejoc.201000484
|View full text |Cite
|
Sign up to set email alerts
|

Platinum‐Catalyzed Regioselective Formation of β‐Alkoxy Ketones from Internal Alkynes

Abstract: A catalytic amount of Zeise's dimer and 15-crown-5 were combined to effectively promote the regioselective formation of β-alkoxy ketones from 2-(homopropargyloxy)ethanols in dimethoxyethane. The desired products were obtained in 59-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Regiocontrolled metal-catalyzed hydrations of alkynes to form carbonyl derivatives are of prime interest in organic synthesis. , Hydrative coupling of an alkyne with another functionality is particularly interesting because it not only introduces a carbonyl group but also allows formation of a C−C bond. Metal-catalyzed three-component couplings are powerful tools to access complicated frameworks, but hydrative carbocyclizations of alkynes are exclusively focused on two-component coupling reactions, including 1, n -diynes, 1-yne-5-enones, 1-en-5-ynes, and 1-allen- n -ynes ( n = 5−7), with rare examples for three-component coupling reactions .…”
mentioning
confidence: 99%
“…Regiocontrolled metal-catalyzed hydrations of alkynes to form carbonyl derivatives are of prime interest in organic synthesis. , Hydrative coupling of an alkyne with another functionality is particularly interesting because it not only introduces a carbonyl group but also allows formation of a C−C bond. Metal-catalyzed three-component couplings are powerful tools to access complicated frameworks, but hydrative carbocyclizations of alkynes are exclusively focused on two-component coupling reactions, including 1, n -diynes, 1-yne-5-enones, 1-en-5-ynes, and 1-allen- n -ynes ( n = 5−7), with rare examples for three-component coupling reactions .…”
mentioning
confidence: 99%
“…Under these conditions, 3p and 3q were obtained in 86 and 83 % yields, respectively. However, it is also possible that, in the presence of hydrated p TSA, 6a and 6b may open up to form the corresponding ketones, and it may be these ring‐opened species that are the actual reaction partners 23. It was also found that the reaction proceeded well under anhydrous conditions; see Equations (5) and (6) below.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, in 2010, Liu reported the platinum-catalyzed regioselective α-hydration of homopropargylic ethers 49 in DME (Scheme 32). 69 After investigating a variety of metal catalysts such as AuCl, Au(PPh 3 )Cl/AgOTf, Hg(OTf) 2 , PtCl 2 , and others, the authors showed that Pt 2 Cl 4 (C 2 H 4 ) 2 (Zeise's dimer 51) gave the best αregioselectivity on a model substrate (80/20). Then, they added various Pt ligands to increase the α/β ratio.…”
Section: α-Regioselectivementioning
confidence: 99%